Adolescent with severe liver disease and positive autoantibodies: when Wilson’s disease presents as autoimmune hepatitis - Modrak, Gabriela (2026)
Wilson’s disease (WD) is an autosomal recessive disorder caused by mutations in the ATP7B gene, leading to impaired copper metabolism. Its clinical presentation is heterogeneous and may mimic autoimmune hepatitis (AIH), making timely diagnosis challenging, particularly in adolescents with severe liver disease of unknown origin. A retrospective descriptive study was conducted based on the medical record review of a patient diagnosed with WD and treated at a university referral hospital. The study was approved by the institutional ethics committee (CEPSH-UFSC, approval no. 7.775.798). A 17-year-old female presented with asthenia, jaundice, and behavior changes. Laboratory findings showed positive autoantibodies, hypergammaglobulinemia, and elevated liver enzymes. Imaging studies revealed chronic liver disease with splenomegaly and Kayser-Fleischer rings. She met criteria for probable AIH and WD according to the Leipzig scoring system. Treatment with prednisone and D-penicillamine led to progressive clinical and biochemical improvement. Genetic testing confirmed compound heterozygosity in the ATP7B gene (p.Pro1273Leu/p.Thr1031Ile). Wilson’s disease can mimic autoimmune hepatitis and should be considered in adolescents presenting with severe liver disease and positive autoantibodies. Early recognition and disease-specific chelating therapy are essential to prevent irreversible liver damage.